Fracture dislocation of the pisiform bone in children: a case report and review of the literature. Issue 6 (November 2015) - Hurni, Yannick; Fusetti, Cesare; de Rosa, Vincenzo
Abstract : Simultaneous fracture and dislocation of the pisiform is a rare condition, and only two cases have been reported in children. We retrospectively collected and reviewed clinical and radiographic data of a child with a type II Salter–Harris fracture of the distal radius, associated with fracture dislocation of the pisiform. In addition, we performed a systematic review of the literature available to date.